Synthesis and Biological Evaluation of Antifungal Triazolyl Haloaromatic Compounds - Krishna Mohan, S. (Asian Journal of Chemistry, 2010)
Antifungal triazolyl haloaromatic compounds 5-9, 13, 14, 16, 17, 19, 20 and 21 were synthesized and evaluated for biological activity. These compounds exhibited moderate activity against Pseudomonas albicans, Aspergillus niger and Candida albicans in comparison with fluconazole in vitro studies.